Surprisingly facile CO2 insertion into cobalt alkoxide bonds: A theoretical investigation - Offermans, Willem K.; Bizzarri, Claudia; Leitner, Walter; Müller, Thomas E. (Beilstein Journal of Organic Chemistry, 2015)
Exploiting carbon dioxide as co-monomer with epoxides in the production of polycarbonates is economically highly attractive. More effective catalysts for this reaction are intensively being sought. To promote better understanding of the catalytic pathways, this study uses density functional theory calculations to elucidate the reaction step of CO2 insertion into cobalt(III)–alkoxide bonds, which is also the central step of metal catalysed carboxylation reactions. It was found that CO2 insertion into the cobalt(III)–alkoxide bond of [(2-hydroxyethoxy)CoIII(salen)(L)] complexes (salen = N,N”-bis(salicyliden-1,6-diaminophenyl)) is exothermic, whereby the exothermicity depends on the trans-ligand L. The more electron-donating this ligand is, the more exothermic the insertion step is. Interestingly, we found that the activation barrier decreases with increasing exothermicity of the CO2 insertion. Hereby, a linear Brønsted–Evans–Polanyi relationship was found between the activation energy and the reaction energy.
Keywords: activation; alkoxide; carbon dioxide; cobalt; insertion; salen